Chiari Network in Right Atrium of Heart - Thapa, Raj Kumar; KC, Kanchan; Khatri, Rishi; Khatri, Devendra (Medical Journal of Shree Birendra Hospital, 2017)
Chiari network is an embryonic remnant of right valve of sinus venosus due to its incomplete resorption. It is a fenestrated net-like membranous structure mostly seen in the right atrium near the opening of Inferior vena cava and Coronary sinus. It is rare, often diagnosed incidentally and is usually of no clinical significance. However, there are reports of its association with atrial fibrillation, arrhythmias, right atrial thrombus entanglement, paradoxical embolism and catheter entrapment during percutaneous interventions. Here we present a case of Chiari network in a 45 years old female diagnosed by two dimensional trans-thoracic echocardiography (2D-TTE). Our aim is to highlight clinical significance of this rare but possible congenital cardiac remnant which is often silent.